(untitled) (Research, Society and Development, 2024)
Introduction: One of the main milestones of pharmaceutical policies in Brazil, which aims to reorient Pharmaceutical Assistance, came from the creation of the National Medicines Policy. From this milestone, health departments began to institutionalize PA in their regions, with this institutionalization process understood as a political-administrative and social procedure. However, in Brazilian municipalities, this process is still considered partial and heterogeneous. Objective: To present data and information from the municipality of Chaves, Pará, on demographic, socioeconomic, epidemiological, management and actions in health and pharmaceutical assistance aspects. Methodology: Exploratory study, descriptive-analytical in nature, retrospective for the years 2020, 2021, 2022 and 2023. Results: Agreeing on PA actions, in a coordinated and integrated manner with the Municipal Health Department, has been providing better governance and management of pharmaceutical assistance. In time, the municipality faces significant difficulties justified by the so-called Amazon factor. Conclusion: The results achieved demonstrated that the municipality of Chaves, Pará, is inserted in a challenging scenario in terms of governance and management of pharmaceutical assistance.